FAKTOR-FAKTOR YANG MEMENGARUHI PENYEBARAN PENYAKIT TUBERKULOSIS (TBC) DI PROVINSI JAWA BARAT - DEWI, NI KADEK ARISKA; SUKARSA, I KOMANG GDE; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2020)
The highest number of tuberculosis sufferers in Indonesia is in West Java Province. The spread of TB disease depends on a variety of different factors in each region. Due to differences in geographical conditions between regions in West Java, the differences between one variable and different variables give different responses at different locations in each study area. This is called spatial heterogeneity. The method that can be used to overcome the problem of spatial heterogeneity is the Weighted Geographic Regression (GWR) method. The best model of this research is the GWR model using the bisquare adaptive kernel weighting function. The resulting coefficient of determination is 93.79%. Significant variables are the number of households having clean and healthy life behavior (PHBS), the number of male residents, and the number of houses not meeting health requirements.